2018
DOI: 10.3892/mmr.2018.9042
|View full text |Cite|
|
Sign up to set email alerts
|

Cryptotanshinone inhibits IgE‑mediated degranulation through inhibition of spleen tyrosine kinase and tyrosine‑protein kinase phosphorylation in mast cells

Abstract: Atopic dermatitis (AD) is a type of chronic skin inflammation and one of the most common relapsing allergic diseases, which presents with a severe rash and itchy skin lesions. The pathogenesis of AD is primarily associated with hyper‑activated mast cells, which makes them an effective treatment target. After cross‑linking the antigen/immunoglobulin (Ig) E complex binds to its high affinity receptor FcεRl on the surface of mast cells. The cells subsequently secrete excessive pro‑inflammatory mediators, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…A histopathological analysis, which involved hematoxylin and eosin (H&E) staining, and a morphometric analysis showed that the DNCB-induced increase in epidermal and dermal thickenings reduced significantly ( p < 0.001, n = 5) upon the topical application of chrysin ( Figure 5 C). Previous studies have reported that DNCB increases the phosphorylation of p65 NF-κB in BALB/c mice models [ 18 , 19 ]. We also observed that the epidermal levels of phosphorylated p65 NF-κB were high in mice challenged with DNCB; however, the levels decreased substantially upon the topical application of chrysin ( Figure 5 D).…”
Section: Resultsmentioning
confidence: 99%
“…A histopathological analysis, which involved hematoxylin and eosin (H&E) staining, and a morphometric analysis showed that the DNCB-induced increase in epidermal and dermal thickenings reduced significantly ( p < 0.001, n = 5) upon the topical application of chrysin ( Figure 5 C). Previous studies have reported that DNCB increases the phosphorylation of p65 NF-κB in BALB/c mice models [ 18 , 19 ]. We also observed that the epidermal levels of phosphorylated p65 NF-κB were high in mice challenged with DNCB; however, the levels decreased substantially upon the topical application of chrysin ( Figure 5 D).…”
Section: Resultsmentioning
confidence: 99%
“…Choiet al reported that tanshinones possibly exert their anti-allergic activities by affecting FcεRI-mediated tyrosine phosphorylation of ERK and PLCγ2 [30]. Buyanravjikh et al reported that cryptotanshinone, a natural compound extracted from Salvia miltiorrhiza Bunge, had an inhibitory effect on IgE/antigen-mediated mast cell degranulation through the inhibition of tyrosine kinase-dependent degranulation signalling pathways [4]. This study demonstrates, for the first time, that tanshinone I is a direct Syk inhibitor and has anti-mast cell degranulation activity in vitro, which may provide a perspective for elucidating the molecular mechanism of tanshinone I for its anti-allergic and other pharmacological effects.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of Syk-mediated immunoreceptor (B-cell receptors, T-cell receptors and Fc receptors) signalling leads to inhibition of mast cells, macrophages and B-cell activation and subsequent release of inflammatory modulators [3]. Recently, Buyanravjikh et al reported that cryptotanshinone could inhibit IgE-mediated mast cell degranulation through theinhibition of tyrosine kinase-dependent degranulation signalling pathways involving Syk and Lyn [4]. Therefore, seeking safe Syk small molecule inhibitors has attracted considerable interest in a number of therapeutic areas, including the treatment of allergic asthma, rhinitis, rheumatoid arthritis and chronic lymphocytic leukaemia [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…plant, the dried root of Salvia miltiorrhiza Bunge) is a common and important Chinese medicine with well-defined phytochemicals. As a type of complementary and alternative medicine, it has been used widely for a long time and shown significant clinical outcomes in terms of anticoagulant, antioxidant, and anti-inflammatory activities to benefits for vascular protection and cancer treatment [710]. The major biologically active components of Danshen include water-soluble phenolic acids and lipophilic tanshinones.…”
Section: Introductionmentioning
confidence: 99%
“…It also has reports indicating that Danshen has excellent anticancer effects, including inhibition of proliferation, restraint of angiogenesis and metastasis, and circumvention of multidrug resistance [9]. For example, Sumiyasuren Buyanravjikh et al [10] found that cryptotanshinone (CRT), a natural product extracted from Danshen, effectively decreased secretion of proinflammatory cytokines including interleukin-1 β and tumor necrosis factor- α . Furthermore, Danshen inhibited hyperproliferative fibroblasts, according to a report [12].…”
Section: Introductionmentioning
confidence: 99%